2019
DOI: 10.1039/c9ra05712a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-phytopathogenic activity of 8-hydroxyquinoline derivatives

Abstract: Phytopathogenic fungi have become a serious threat to the quality of agricultural products, food security and human health globally, necessitating the need to discover new antifungal agents with de novo chemical scaffolds and high efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Pippi et al (2019a), found that this molecule's mechanism for action, possibly, takes place at the cell wall level, causing morphological changes in fungal cells. Similar results were obtained by Yin et al (2019), who observed the appearance of fungal cells treated with another 8HQ derivative pattern synthesized by the group. The effectiveness of PH 151 in controlling phytopathogenic fungi has been tested for the first time in this study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Pippi et al (2019a), found that this molecule's mechanism for action, possibly, takes place at the cell wall level, causing morphological changes in fungal cells. Similar results were obtained by Yin et al (2019), who observed the appearance of fungal cells treated with another 8HQ derivative pattern synthesized by the group. The effectiveness of PH 151 in controlling phytopathogenic fungi has been tested for the first time in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Derivatives of 8HQ were synthesized and tested in vitro by Yin et al (2019). This highlighted compound 2, which was able to totally inhibit the mycelial growth of the five species of phytopathogenic fungi tested, at a concentration of 25 µg ml À1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEM observations were conducted according to the method of previous work with minor modifications [29,44]. Briefly, 5 mm diameter mycelial disks of F. oxysporum f.sp.…”
Section: Scanning Electron Microscope (Sem) Observationsmentioning
confidence: 99%
“…Natural and synthetic quinoline nucleus containing compounds endowed a broad spectrum of biological activities [7,8]. Quinoline derivatives displayed vital pharmacological activities such as antimalarial [9,10], antimicrobial [11,12], antifungal [13,14], antitubercular [15,16], anticancer [17,18], antiviral [19,20], antiinflammatory and COX inhibitors [21,22], carbonic anhydrase inhibitors [23], antileishmanial [24], PIM inhibitors [25], anticonvulsant, and antihypertensive [26] activities. Thiazole is the important scaffold of several bioactive natural products [27,28] and reported broad spectrum of biological activity such as antibacterial [29,30], inflammatory [31], antifungal [32,33], antitubercular [34,35], antimalarial [36], anticancer [37], antiviral [38], and CNS active agents [39].…”
Section: Introductionmentioning
confidence: 99%